The Service Revolution in South Asia - World Bank (Washington, DC, 2014)
The story of Hyderabad, the capital of the Indian state Andhra Pradesh, is truly inspiring for late-comers to development. Within two decades, Andhra Pradesh has been catapulted straight from a poor and largely agricultural economy into a major service center. It has transformed itself from a lagging into a leading region. Fuelled by an increase in service exports of 45 times between 1998 and 2008, the number of information technology companies in Hyderabad increased eight times, and employment increased 20 times. Service-led growth has mushroomed in other parts of India and South Asia as well. Indeed, growth in the services sector has enabled South Asia to grow almost as fast as East Asia in this century, with growth of just under seven percent annually between 2000 and 2007. Growth rates in South Asia and East Asia have converged. The two fastest growing regions in the world, however, have very different growth patterns. While East Asia is a story of growth led by manufacturing, South Asia has thrived on service-led growth. The promise of the services revolution is that countries do not need to wait to get started with rapid development. There is a new boat that development late-comers can take. The globalization of service exports provides alternative opportunities for developing countries to find niches, beyond manufacturing, where they can specialize, scale up and achieve explosive growth, just like the industrializes. The core of the argument is that as the number of goods and services produced and traded across the world expand with globalization, the possibilities for all countries to develop based on their comparative advantage expand. That comparative advantage can just as easily be in services as in manufacturing or indeed agriculture.